Clinical Application of a Bird-Beak-Type Z-Shaped Asymmetrical Flap in the Reconstruction of the Inner Canthus - Huang, Ze-Chun; Yan, Dan; Huang, Li-Fang; Yang, Hao-Yan; He, Bin; Zhang, An-Li; Li, Shuai-Hua (Frontiers in Surgery, 2022)
Objective: To introduce a new surgical method for the repair of an overlarge inner canthus combined with tissue loss at the inner canthal angle by using a bird-beak type z-shaped asymmetric flap and to summarize its clinical effect. Method: A total of 56 patients with an overlarge inner canthus were randomly selected, and the bird-beak type z-shaped asymmetric flap was used on the nasal side of the lower eyelid to repair and reconstruct the inner canthal folds. According to the physiological aesthetics of the inner canthus, the inner canthal point was located. The short and long arms of the z-shaped asymmetric flap were separated, replaced, fixed, and shaped to reconstruct the skin folds of the inner canthus and restore its aesthetic morphology. Result: All incisions after surgery achieved primary healing, and all 56 cases were followed up for 6–20 months (average 8.6 months). The carunculae lacrimalis were moderately exposed, the inner canthal angles possessed a natural appearance, and the results of the surgery were satisfactory. Five patients developed scar hyperplasia within one month after surgery, and arnica gel was applied topically for 3–6 months until the scar faded or disappeared, but no obvious scars were seen in the surgical area of the remaining patients. In two patients, the internal canthi were asymmetrical, but this improved after adjustment. Conclusion: Repair of the overlarge inner canthus and tissue loss at the inner canthal angle using the bird-beak type z-shaped asymmetric flap is a simple operation resulting in minimal trauma. Postoperatively, the inner canthal angle possessed a natural appearance with no obvious scarring.